Continuum Analysis of Biological Systems Conserved Quantities, Fluxes and Forces - Suraishkumar, G.K (Biosystems & Biorobotics, 2014)
This book addresses the analysis, in the continuum regime, of biological systems at various scales, from the cellular level to the industrial one. It presents both fundamental conservation principles (mass, charge, momentum and energy) and relevant fluxes resulting from appropriate driving forces, which are important for the analysis, design and operation of biological systems. It includes the concept of charge conservation, an important principle for biological systems that is not explicitly covered in any other book of this kind. The book is organized in five parts: mass conservation; charge conservation; momentum conservation; energy conservation; and multiple conservations simultaneously applied. All mathematical aspects are presented step by step, allowing any reader with a basic mathematical background (calculus, differential equations, linear algebra, etc.) to follow the text with ease. The book promotes an intuitive understanding of all the relevant principles and in so doing facilitates their application to practical issues related to design and operation of biological systems. Intended as a self-contained textbook for students in biotechnology and in industrial, chemical and biomedical engineering, this book will also represent a useful reference guide for professionals working in the above-mentioned fields.    .